2006
DOI: 10.2134/jeq2005.0447
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Land Use on Soil Health Indicators in Peri‐Urban Agriculture in the Humid Forest Zone of Southern Cameroon

Abstract: The objective of this study was to identify the effect of different land uses in peri-urban agriculture on the soil properties. Soil health indicators were evaluated in the top 10 cm at five tilled agricultural sites involving different cropping systems and use of agrochemicals within the peri-urban agricultural areas of Yaounde, Cameroon, and compared with a native forest land. The experimental data showed that the selected indicators were sensitive to cropping practice. Most cropped land had significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
0
15
0
4
Order By: Relevance
“…However, in the present study, we did not find any such correlation. The MBC to organic matter ratio is thought to be indicative of the organic-matter quality and availability (Monkiedje et al 2006). Our results showed that the ratio was greatest in turf and lowest in pasture (Table 2), which probably suggested that turf had the most chemical diversity in organic-matter sources and efficiency of C utilization and that conversely the pasture soil had the least.…”
Section: Microbial Community Dynamicsmentioning
confidence: 65%
See 1 more Smart Citation
“…However, in the present study, we did not find any such correlation. The MBC to organic matter ratio is thought to be indicative of the organic-matter quality and availability (Monkiedje et al 2006). Our results showed that the ratio was greatest in turf and lowest in pasture (Table 2), which probably suggested that turf had the most chemical diversity in organic-matter sources and efficiency of C utilization and that conversely the pasture soil had the least.…”
Section: Microbial Community Dynamicsmentioning
confidence: 65%
“…Therefore, changes in land uses with different intensity or history of agricultural practices consequently results in distinctive changes in microbial community composition and function (Grayston et al, 2004). Land-use changes can also disrupt carbon (C) and nitrogen (N) dynamics and organic-matter storage in soils across a range of habitats (Garcia-Oliva, Lancho, and Montano 2006; Monkiedje et al 2006), which are commonly viewed as major factors causing shifts in microbial community composition (Schimel and Bennett 2004;Cookson et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Slight 294 F. Begum et al differences in P could be due to inputs of organic manure and chemical fertilized in main cropping season (premonsoon) on agricultural land. Monkiedje et al (2006) found significantly higher available P and pH in cropland than in the forested soils. Available P was also somewhat higher on the north-rather than the south facing slope.…”
Section: Seasonal Dynamics Slope Aspect and Land Use Effects On Soilmentioning
confidence: 77%
“…La actividad fenoloxidasa esta relacionada con la taza degradación vegetal en el mantillo, por lo que está influenciada directamente con el tipo de vegetación y su expresión está ligada a la disponibilidad de nutrientes. Se ha observado (Monkiedje et al, 2006) que el incremento de nutrientes (nitrógeno y fósforo) en el suelo, por diferentes prácticas agrícolas orgánicas y convencionales, tienen efectos negativos sobre la actividad fenol oxidasa. En ecosistemas acuáticos naturales la introducción de dichos nutrientes, tienen influencia negativa sobre la actividad fenol oxidasa (Penton y Newman, 2008) la que se vio acompañada de disminución en la diversidad vegetal.…”
Section: Indicadores De Salud Y Calidad De Suelosunclassified
“…Posiblemente existe una relación entre la actividad deshidrogenasa y los contenidos de carbono activo que se determinaron en el sistema Córdoba-Juan Amarillo, relación que anteriormente ha sido documentada (Caravaca et al, 2005;Jezierska-Tys y Frńc, 2009;Peruzzi et al, 2011), también se han observado (Monkiedje et al, 2006) incrementos…”
Section: Indicadores De Salud Y Calidad De Suelosunclassified